The antioxidant activity of polysaccharides from Armillaria gallica - Su, Peiwen; Qiu, Honghao; Liang, Lishan; Weng, Luo; Liu, Yingjie; Liu, Jiajun; Wu, Liyan; Meng, Fanxin (Frontiers in Nutrition, 2024)
The purpose of this study was to investigate the antioxidant activity of Armillaria gallica polysaccharides. It explored whether Armillaria gallica polysaccharides (AgP) could prevent HepG2 cells from H2O2-induced oxidative damage. The results demonstrated that HepG2 cells were significantly protected by AgP, and efficiently suppressed the generation production of reactive oxygen species (ROS) in HepG2 cells. Additionally, AgP significantly decreased the abnormal leakage of alanine aminotransferase (ALT) and lactate dehydrogenase (LDH) caused by H2O2, protecting cell membrane integrity. It was discovered that AgP was also found to regulate the activities of antioxidant enzymes, superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-PX), while reducing the levels of malondialdehyde (MDA), thus protecting cells from oxidative damage. According to the flow cytometry analysis and measurement of caspase-3, caspase-8, and caspase-9 activities, AgP could modulate apoptosisrelated proteins and attenuate ROS-mediated cell apoptosis.